Caring and community : concepts and models for service-learning in nursing - Norbeck, Jane S.; Connolly, Charlene; Koerner, JoEllen Goertz; American Association for Higher Education; Community-Campus Partnerships for Health (Washington, DC : American Association for Higher Education, 1998)
Abstract from ERIC database describing version attached as PDF: This volume is part of a series of 18 monographs on service learning and the academic disciplines. These essays focus on nursing, examining partnerships between education and service, nurse and person, and profession and community. Chapters describe both theoretical and experiential ways in which nursing has begun to incorporate service-learning as a methodology in many diverse settings and with many communities of interest. Following the Introduction by Jane S. Norbeck, Charlene Connolly, and Jo Ellen Koerner, three theoretical essays include: "Humanistic Learning in the Context of Service: The Liberal Arts in Nursing Education" (Jean E. Bartels); "Preparing Nurses for Roles That Will Improve Community Health: Two National Programs Enhance Relationships between Providers and Educators" (Mary Kay Kohles, Maryalice Jordan-Marsh, and Margaret T. McNally); and "Service Education Partnerships Create Community Service-Learning Opportunities in a Rural Region" (Sharon P. Aadalen, Mary Kay Hohenstein, Mary I. Huntley, and Annette J. McBeth). Seven essays on classroom applications follow, including: "Service-Learning as a Pedagogy in Nursing" (Elaine Cohen, Susan Johnson, Lois Nelson, and Connie Peterson); "Case Study of a Service-Learning Project in a Nurse-Managed Clinic for Homeless and Indigent Individuals" (Carol L. Macnee, Deborah H. White, and Jean C. Hemphill); "A Case Study in Service-Learning Using a Collaborative Community-Based Caring Model" (Evelyn C. Atchison and Patricia A. Tumminia); "Community Empowerment through Service-Learning" (Leanne C. Busby, Cathy Taylor, and Linda Norman); "Nursing Clinical Education in an Urban Public School System" (Donna Miles Curry, Kimberley X. Hickok, and Kate Cauley); "The Community as Classroom: Service-Learning in Tillery, North Carolina" (Nina P. Shah and Mary A. Glascoff); and "Service-Learning Lessons from the Chambered Nautilus" (Evelyn D. Quigley, Betty Sayers, and Ruth Hanson). Sets of samples syllabi and assignments are provided for four of the essays. A 65-item annotated bibliography, organized by topic, and a list of practitioners is appended. (All papers contain references.) (SM).
Humanistic learning in the context of service : the liberal arts in nursing education / Jean E. Bartels -- Preparing nurses for roles that will improve community health : two national programs enhance relationships between providers and educators / Mary Kay Kohles, Maryalice Jordan-Marsh and Margaret T. McNally -- Service education partnerships create community service-learning opportunities in a rural region / Sharon P. Aadalen [and others] -- Service-learning as a pedagogy in nursing / Elaine Cohen [and others] -- Case study of a service-learning project in a nurse-managed clinic for homeless and indigent individuals / Carol L. Macnee, Deborah H. White and Jean C. Hemphill -- A case study in service-learning using a collaborative community-based caring model / Evelyn C. Atchison and Patricia A. Tumminia -- Community empowerment through service-learning / Leanne C. Busby, Cathy Taylor and Linda Norman -- Nursing clinical education in an urban public school system / Donna Miles Curry, Kimberley X. Hickok and Kate Cauley -- The community as classroom : service-learning in Tillery, North Carolina / Nina P. Shah and Mary A. Glascoff -- Service-learning lessons form the chambered nautilus / Evelyn D. Quigley, Betty Sayers and Ruth Hanson -- Materials from "service-learning as a pedagogy in nursing" / Elaine Cohen [and others] -- Materials from "case study of a service-learning project in a nurse-managed clinic for homeless and indigent individuals" / Carol L. Macnee, Deborah H. White and Jean C. Hemphill -- Materials from service-learning courses on homelessness and rural nursing / Suzanne MacAvoy, Paul E. Carrier and Elizabeth Gardner -- Materials from service-learning practica in nursing service administration / Linda Workman, L. Sue Davis and Darlene A. Anderson.
Annotated bibliography: pages 169-180.
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Nursing -- Study and teaching; Community health nursing; Rural health services; MEDICAL -- Nursing -- Research & Theory; Community health nursing; Nursing -- Study and teaching; Rural health services; Community Health Nursing; Health & Biological Sciences; Nursing; Electronic book; Electronic books